THE ROLE OF TECHNOLOGY INTEGRATION IN ENHANCING TEACHER TRAINING PROGRAMS: A FOCUS ON PEDAGOGICAL (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The integration of pedagogical approaches and information and communication technologies (ICT) has transformed teacher training methodologies. This article explores the potential of combining these two fields to enhance the professional competencies of aspiring teachers. It examines the role of ICT in modern educational practices, highlights the benefits and challenges of incorporating technology into teacher training programs, and offers strategies for effective implementation. The findings underscore the importance of a balanced approach that merges traditional teaching methods with cutting-edge digital tools to foster more dynamic, adaptive, and student-centered learning environments.